2016
DOI: 10.1007/s40899-016-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of the proposed alternatives of inter-basin water transfer from the Baro Akobo to Awash basin in Ethiopia

Abstract: Water resources in Ethiopia are relatively skewed towards basins with rivers flowing to the west and southwest. Baro Akobo, which is a part of the eastern Nile River basin, is a west-flowing river with water availability of about 3432 m 3 per person per year. Awash basin in the east is a water-deficit basin with just about 325 m 3 per person. This study identifies and analyses the three possible alternatives of water transfer from Baro Akobo to Awash basin in Ethiopia. The first proposed link is about 685 km l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The basin is already subject to water stress, with higher water demand than supply. For instance, a study by [4] estimated an average annual runoff of 4640 MCM (million cubic meter) while the average annual demand is 4670 MCM. The basin is subject to high intra-annual variability, with dry season water shortage recognized as a challenge for various activities such as irrigation and domestic water supply by the Awash Basin Authority [5].…”
Section: Introductionmentioning
confidence: 99%
“…The basin is already subject to water stress, with higher water demand than supply. For instance, a study by [4] estimated an average annual runoff of 4640 MCM (million cubic meter) while the average annual demand is 4670 MCM. The basin is subject to high intra-annual variability, with dry season water shortage recognized as a challenge for various activities such as irrigation and domestic water supply by the Awash Basin Authority [5].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrological water balance analysis of the Lake Tana Basin in Ethiopia indicated that base flow is an important component of the total discharge within the study area that contributes more than the surface runoff [18]. Radar rainfall data is useful in distributed hydrologic studies and was used as data input in the SWAT for application in flood analysis and prediction [19,20], and in addressing model response to extreme weather events and improving water resources distribution [21].…”
Section: Applications Considering Water Resources and Streamflow Simulationsmentioning
confidence: 99%
“…178 The regional government of Oromia is investing in its own irrigation projects in Fentale and Tibila, with no reference to upstream and downstream users. 179 In the Awash Basin, competing and conflicting interests of 173 180 A number of studies have attributed the cause of conflicts in the Awash River Basin to the introduction of various large scale commercial agricultural schemes along river courses. 181 This prompts a question whether the regional states in the basin can, from the outset make decisions on development activities over such inter-state water resources such as Awash, which is within the exclusive mandate of the federal government.…”
Section: Inter-state Water Dispute Resolutionmentioning
confidence: 99%